2014
DOI: 10.1007/s11005-014-0709-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrability of the Bi-Yang–Baxter σ-Model

Abstract: We identify the r-matrix governing the Poisson brackets of the matrix elements of the Lax operator of the bi-YB-WZ model. IntroductionStrong integrability is the property of certain Lax integrable theories. It amounts to Poissoncommutativity of the integrals of motions which are obtained as the spectral invariants of the Lax operator. In this paper, we focus on the issue of the strong integrability of Lax integrable non-linear σ-models.The epitome of the Lax integrable non-linear σ model is the principal chira… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(158 citation statements)
references
References 55 publications
8
143
1
Order By: Relevance
“…Indeed, the computation of the corresponding RG flow equations using gravitational methods was performed in [2,3] and is in agreement with results from field theoretical methods [8][9][10]. Furthermore, it was shown that these models, named generically as λ-deformed, can be embedded in specific cases of low dimensionality to supergravity [11][12][13][14][15], while their relation to η-deformations for group and coset spaces introduced in [16][17][18] and [19][20][21] respectively, via Poisson-Lie T-duality [22] and appropriate analytic continuations, was uncovered in [23][24][25][26][27]. More recently, the computation of the all-loop correlators for the…”
Section: Jhep03(2017)083supporting
confidence: 71%
“…Indeed, the computation of the corresponding RG flow equations using gravitational methods was performed in [2,3] and is in agreement with results from field theoretical methods [8][9][10]. Furthermore, it was shown that these models, named generically as λ-deformed, can be embedded in specific cases of low dimensionality to supergravity [11][12][13][14][15], while their relation to η-deformations for group and coset spaces introduced in [16][17][18] and [19][20][21] respectively, via Poisson-Lie T-duality [22] and appropriate analytic continuations, was uncovered in [23][24][25][26][27]. More recently, the computation of the all-loop correlators for the…”
Section: Jhep03(2017)083supporting
confidence: 71%
“…It would be very interesting to clarify the correspondence between the list in [90][91][92] and our results. 13 It would be most important to generalize our argument to 10D Minkowski spacetime in order to extend our argument to a consistent string theory. For this purpose, we have to consider the 10D conformal group SO(2, 10) and realize 10D Minkowski spacetime as a slice of 11D AdS space.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
“…Deformations of S 3 and AdS 3 have been well investigated [8][9][10][11][12][13][14][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. 1 A systematic way is the Yang-Baxter sigma model approach proposed by Klimcik [11][12][13].…”
Section: Jhep10(2015)185mentioning
confidence: 99%
“…The Yang-Baxter sigma-model description is known as a systematic way to study integrable deformations of 2D integrable non-linear sigma models [1][2][3]. It was originally proposed for principal chiral models on the basis of the modified classical Yang-Baxter equation (mCYBE) .…”
Section: Introductionmentioning
confidence: 99%